1993
DOI: 10.1007/bf00920477
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of arachidonic acid (AA)- and tetradecanoylphorbol acetate (TPA)-induced dermal inflammation

Abstract: The effects of topical application of arachidonic acid (AA) or phorbol ester, tetradecanoylphorbol 13-acetate (TPA), on edema response, vascular permeability, MPO, NAG, and generation of eicosanoids were studied in two murine models of cutaneous inflammation. AA produced a short-lived edema response with a rapid onset that was associated with marked increases in levels of prostaglandins (PGE2, 6-keto-PGF1 alpha, PGF2 alpha), thromboxane B2 (TxB2) and leukotriene B4 (LTB4), with smaller increases in levels of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
180
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(192 citation statements)
references
References 22 publications
7
180
0
2
Order By: Relevance
“…Role of PGE 2 -EP3 signaling in AA-induced and PGE 2 -induced hyperpermeability It was previously reported that lipid mediators synthesized by COX pathways are involved in AA-induced inflammation, and that PGE 2 was abundantly synthesized within ear tissues upon AA application (37). Indeed, also in our experimental settings, aspirin significantly suppressed AA-induced hyperpermeability (Fig.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Role of PGE 2 -EP3 signaling in AA-induced and PGE 2 -induced hyperpermeability It was previously reported that lipid mediators synthesized by COX pathways are involved in AA-induced inflammation, and that PGE 2 was abundantly synthesized within ear tissues upon AA application (37). Indeed, also in our experimental settings, aspirin significantly suppressed AA-induced hyperpermeability (Fig.…”
Section: Resultssupporting
confidence: 71%
“…1E). Application of AA has been shown to induce the production of a broad range of eicosanoids such as PGE 2 (37). We therefore examined the direct effect of exogenous PGE 2 on vascular permeability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme activates other enzymatic pathways such as phospholipase A2 (PLA2) and mitogen activated protein kinases (MAPK), resulting in release of platelet activation factor (PAF) and arachidonic acid. These events either induce vasodilatation, vascular permeability, and secretion of serotonin and histamine or stimulate synthesis of prostaglandins and leukotrienes by cyclooxygenase (COX) and 5-lipoxygenase (5-LOX) enzymes, respectively (Carlson et al, 1985;Fischer et al, 1988;Rao et al, 1993). Based on this, one possible mechanism for the anti-inflammatory effects of the extract, in the TPA model, is its interaction with the infiltration of leucocytes (according to the pathological results) and regulation of release or function of inflammatory eicosanoids.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when AA was applied to the mouse ear, the vascular permeability preceded the edemic response and neutrophil influx. Furthermore, TPA induced longer lasting edema associated with marked influx of neutrophils, whereas AA induced a short-lived edemic response with rapid onset associated with marked increases in the levels of oxidized fatty acids 29 . These pathways with some distinction between TPA and AA may reflect a biological difference such as the TRPV3 response.…”
Section: Discussionmentioning
confidence: 96%